Analisis Konsep Bunga dalam Matematika dan Kaitannya dengan Praktik Riba dalam Ekonomi Islam - Cici Utami Salamah; Syahidin (Jurnal Ilmiah Ekonomi Islam, 2026)
The concept of interest in financial mathematics plays an important role in various modern financial activities, but its meaning often conflicts with Islamic economic principles that prohibit usury. This study aims to analyze the fundamental differences between the concept of interest as a mathematical calculation instrument and usury as an additional practice that is unlawful in debt transactions according to Islamic law. Using a qualitative approach through a literature review method, this study examines the theories of simple and compound interest in mathematics as well as the views of Islamic jurisprudence and economics on usury. The findings show that interest in mathematics is neutral because it functions as a model for the growth of money value, both linearly and exponentially. Conversely, usury is considered harmful because it causes injustice, excessive financial burdens, and imbalances between lenders and borrowers. The study also found similarities between high interest rates on online loans and the characteristics of al-nasi’ah (deferred usury), mainly due to additional charges that continue to increase due to delayed payments. This study provides a conceptual understanding that links mathematical approaches and Sharia perspectives, and emphasizes the importance of financial literacy and understanding Islamic principles in financial decision-making. Further research is needed to evaluate the application of Sharia financial instruments as a more equitable and sustainable alternative system for society.